Increasing Human Capital by Electrifying Health Centers and Schools through Off-Grid Solar Solutions - Elahi, Raihan (World Bank, Washington, DC, 2020)
The electrification of health centers, schools, and other public institutions has been limited by the slow expansion of national grids, which has staggering consequences for economic growth, poverty reduction, and the accumulation of human capital. Off-grid solar solutions have enormous potential to address the problem, both in Sub-Saharan Africa and across the world, but simply purchasing and installing the units without providing for adequate maintenance is not effective. Installing stand-alone solar units and servicing them through long-term performance-based contracts can give public institutions the electricity service they need at a cost governments can afford.